Are We Drunk Yet? Motor Versus Cognitive Cues of Subjective Intoxication. (7th October 2013) - Celio, Mark A.; Usala, Julie M.; Lisman, Stephen A.; Johansen, Gerard E.; Vetter‐O'Hagen, Courtney S.; Spear, Linda P.
<x xml:space="preserve">Abstract</x> Background Perception of alcohol intoxication presumably plays an important role in guiding behavior during a current drinking episode. Yet, there has been surprisingly little investigation of what aspects associated with intoxication are used by individuals to attribute their level of intoxication. Methods Building on recent laboratory‐based findings, this study employed a complex field‐based design to explore the relative contributions of motor performance versus cognitive performance—specifically executive control—on self‐attributions of intoxication. Individuals recruited outside of bars (N = 280; mean age = 22; range: 18 to 32) completed a structured interview, self‐report questionnaire, and neuropsychological testing battery, and provided a breath alcohol concentration (BrAC) sample. Results Results of a multiple linear regression analysis demonstrated that current level of subjective intoxication was associated with current alcohol‐related stimulant effects, current sedative effects, and current BrAC. After controlling for the unique variance accounted for by these factors, subjective intoxication was better predicted by simple motor speed, as indexed by performance on the Finger Tapping Test, than by executive control, as indexed by performance on the Trail Making Test. Conclusions These results—generated from data collected in a naturally occurring setting—support previous findings from a more traditional laboratory‐based investigation, thus illustrating the iterative process of linking field methodology and controlled laboratory experimentation.